Optimal monetary policy with the risk-taking channel - Angela Abbate; Dominik Thaler (European Central Bank (ECB), 2023)
Empirical research suggests that lower interest rates induce banks to take higher risks. We assess analytically what this risk-taking channel implies for optimal monetary policy in a tractable New Keynesian model. We show that this channel creates a motive for the planner to stabilize the real rate. This objective conflicts with the standard inflation stabilization objective. Optimal policy thus tolerates more inflation volatility. An inertial Taylor-type reaction function becomes optimal. We then quantify the significance of the risk-taking channel for monetary policy in an estimated medium-scale extension of the model. Ignoring the channel when designing policy entails non-negligible welfare costs (0.7% lifetime consumption equivalent).
Keywords: E44; E52; 330; Risk-taking channel; Optimal monetary policy; Inertial policy rate